Підвищення охолоджувальної спроможності градирні за рахунок збільшення поверхні охолодження при розпилюванні води відцентровими форсунками - Dubrovskyi V.V.; Pidvysotskyi O.M.; Bashtovyi A.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2006)
We have carried out an investigation of the effect of geometrical sizes of centrifugal atomizers and the modes of water outflow on the disperse composition of atomized drops. The cooling surface of drops depending on their fractional composition has been evaluated. We have established the factors with the maximum influence on the disperse composition and cooling surface. Empirical correlations for the distribution functions of drops by sizes and a formula for the maximum size of drops have been found.